Surgical decompression for endocrine ophthalmopathy: state-of-the-art - A.A. Krylova; O.I. Krivosheina (РМЖ "Клиническая офтальмология")
A.A. Krylova, O.I. Krivosheina Siberian State Medical University, Tomsk, Russian Federation The article addresses historical overview of surgical techniques for orbital decompression in patients with endocrine ophthalmopathy over the last century. The authors discuss available surgical approaches and techniques for orbital decompression, indications, and potential complications. Surgical techniques for endocrine ophthalmopathy include bony orbitotomy and internal orbital decompression which usually involves the resection of periocular fat. Currently, transpalpebral, transconjunctival, and endonasal approaches are used to reach orbit and its walls. Surgical volume of orbital wall resection depends on exophthalmos severity. Partial resection of internal and inferior orbital walls is less traumatic procedure. However, analysis of the efficacy of available techniques for orbital decompression for endocrine ophthalmopathy demonstrates that exophthalmos significantly improves after the resection of two or more orbital walls only. Considering this, trans-ethmoidal endonasal orbital decompression with the resection of medial and inferior orbital walls characterized by minimal invasiveness, lack of skin incisions and surgical scars is the first choice. The choice of surgical strategy and surgical volume in endocrine ophthalmopathy depends on the s everity of clinical manifestations, expected clinical functional outcomes, and risks of potentional complications. Keywords: endocrine ophthalmopathy, edematous exophthalmos, orbital decompression, external orbitotomy, trans-ethmoidal endonasal orbital decompression, internal orbital decompression. For citation: Krylova A.A., Krivosheina O.I. Surgical decompression for endocrine ophthalmopathy: state-of-the-art. Russian Journal of Clinical Ophthalmology. 2019;19(3):154–158. About the authors: Anna A. Krylova — MD, PhD, Assistant of the Department of Ophthalmology, ORCID iD 0000-0001-8009-6302; Olga I. Krivosheina — MD, PhD, Professor, Head of the Department of Ophthalmology, ORCID iD 0000-0001-7509-5858. Siberian State Medical University. 2, Moscow tract, Tomsk, 634050, Russian Federation. Contact information: Anna A. Krylova, e-mail: krilovane@yandex.ru. Financial Disclosure: no authors have a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 22.02.2019.